First-line biologic treatment of inflammatory bowel disease during the first 12 months after diagnosis from 2010 to 2016: a Norwegian nationwide registry study. (3rd October 2021) - Anisdahl, Karoline; Svatun Lirhus, Sandre; Medhus, Asle W.; Moum, Bjørn; Melberg, Hans Olav; Høivik, Marte Lie
Abstract: Objectives: The use of biologic therapy in inflammatory bowel disease (IBD) is likely to increase with lower costs and more biologics and biosimilars becoming available. Our aim was to estimate the trends in use of first-line biologics during the first year after diagnosis in a Norwegian IBD population from 2010 to 2016. Methods: Data were collected from the Norwegian National Patient Registry and Norwegian Prescription Database. Patients defined as incident IBD cases between 2010 and 2016 were included and followed for 12 months. Patients were stratified by year of diagnosis to examine change over time. Chi-square test was used for calculations on proportions. Time from diagnosis to first biologic was calculated by Kaplan-Meier failure estimates. Results: 14, 645 patients were included, 5283 (36%) with Crohn's disease (CD) and 9362 (64%) with ulcerative colitis (UC). In the 2010 and 2016 cohort, the proportion initiating biologics increased from 17% to 33% ( p  < .001) for CD and 7% to 13% ( p  < .001) for UC. The most frequently used first-line biologics were infliximab (CD: 64% and UC: 82%) and adalimumab (CD: 36% and UC: 15%). The highest registered use of adalimumab was in the 2012 cohort (CD: 56% and UC: 39%). In the 2014–2016 cohorts, infliximab was the most used first-line biologic for both CD and UC. Conclusions: The proportion of IBD patients initiating biologics within 12 months after diagnosis increased between 2010 and 2016. The use of infliximab as first-line biologic increased after the approval of biosimilar infliximab in 2013.